Hyper Smart Cart As Hypermart Business Process Improvement In Minimizing In-Efficiency At The Cashier - Muhammad Muharrom Al Haromainy; Aviolla Terza Damaliana; Abdul Rezha Efrat Najaf; Reisa Permatasari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2022)
The world today has a rapidly growing human population whose daily needs are certainly increasing. Supermarket is a place to fulfill daily needs. When going to the supermarket, we have to spend a lot of time both shopping and also queuing at the cashier. This turns out to be a problem for customers because it can take up customers' time which is also experienced by one of the largest supermarkets, namely Hypermart. Not only a problem for customers, but it can also create a threat to Hypermart companies. However, with advances in technology and information systems, the world is growing to adapt to current conditions, namely by improvising. The improvisation carried out in this research is the payment transaction business process at Hypermart, namely by implementing the Self-CheckOut system by replacing the old trolley with a "Hyper Smart Cart" as an improvisation which will certainly answer all existing problems.